ANALISIS KRITIS HADITS TENTANG SIFAT MUKMIN DENGAN PENDEKATAN SIMULTAN DAN PERSPEKTIF MULTIKULTURAL - Moch. Bachrurrosyady Amrulloh (Akademika, 2019)
This article is aimed at finding out and understanding the quality and the meaning of hadith with a simultaneous approach. This research raises the questions on what the hadith research method with a simultaneous approach is? and what the quality of the hadith about "two traits which are not present in a true believer, namely stingy and bad manner" in simultaneous research is? The Abu Sa'id Al-Khudri’s hadith narrated by Al-Bukhari in the da'if al-isnad by Muhammad Nasiruddin Al-Bani with the quality of da'if al-isnad. In the hadith there are 5 narrators, namely: Muslim, Abu Maghirah al-Salami, Malik bin Dinar, Abdullah bin Ghalib al-Khadari, and Abi Sa'id al-Khudri. Data about the hadith and the quality of the narrators is collected through a documentation method. The data is then analyzed using the content analysis method. In its partial analysis, it was found that: 1. Of all five narrators in the hadith there is only one, namely Abu Said al-Khudri with the quality of thiqah. 2. The sanad is included in the chapter mu'an'an leading to the so-called inqita’ul sanad. 3. The hadits matan was apparently not shad, for not being opposed to the naqli arguments, both the Qur'an and the hadits traditions of a higher quality of sanad. 4. Hadits matan is also not related to the illat, for not being opposed to the aqli arguments such as reason, common sense, history, and science. Thus the Abi Sa'id al-Khudri's hadith concluded by al-Bukhari is a qualified da'if fil isnad in partial research. 5. Based on the hadith tabi’ tsiqah, it is very rarely found that its quality is sahih al isnad because there were some not considered thiqah. So from the four hadits, its tabi' is not able to improve the quality of the mutaba’ hadith, namely the Abu Sa'id Al-Khudri's hadits narrated by Al-Bukhari. Thus it means that the tabi' hadits has not to do with the quality of the mutaba hadits, namely: da'if al-isnad. 6. Because it has 4 shahid hadits of good quality. So based on the research of the hadith on other multi sanad (syawahid), the quality of the hadith is regarded sahih li ghayrihi.